DECONSTRUCTION IN THE SHORT STORY BURUNG KECIL DAN HUJAN BY YANUSA NUGROHO - Winarti, Winarti; Erlinawati, Mira (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2025)
This study explores the concept of deconstruction within the short story Burung Kecil dan Hujan by Yanusa Nugroho, applying poststructuralist theory to uncover how binary oppositions, decentering, and differance are utilized to challenge established meanings and hierarchies. Deconstruction, a method pioneered by Derrida, questions fixed values, revealing the fluidity and instability of meaning within texts. By identifying binary oppositions and analyzing how they are dismantled, this research examines the displacement of traditional centers of power in the narrative. Through the concept of differance, the analysis highlights how meanings in the text remain open to multiple interpretations, destabilizing conventional understandings. This qualitative study aims to deepen the appreciation of poststructuralist methods in literature, demonstrating how Burung Kecil dan Hujan resists fixed interpretations and presents a space for new readings of cultural narratives.